The Prevention of Violent Radicalization as the Most Effective Method Against International Terrorism: The Case of Jihadism (Comillas Journal of International Relations, 2023)
Radicalization processes in relation to violence and terrorist violence occur both in radicalization processes that lead to violence in extreme right-wing, left-wing, ethno-nationalist and separatist groups, in political-religious movements, and in those motivated by a single-issue.Understanding the processes of reciprocal radicalization, the social milieu of people who live in lathes where radicalization processes can occur is essential, as well as the relevance of social networks; all this, in addition to other factors, plays an important role when analysing the processes of radicalization and its prevention.This article focuses on the analysis of the radicalization processes that lead to terrorist violence, analysing the different measures that have been carried out in this field; and making proposals that we think are necessary to prevent the previous phases that lead to the commission of a terrorist act, focusing more on radicalization towards violence in violent radical Islamist jihadist groups.
Keywords: radicalization; terrorism; prevention; jihadism